Emergence and universality in the regulation of stem cell fate. Issue 5 (October 2017) - Rulands, Steffen; Simons, Benjamin D.
Abstract: The mechanisms that control cell fate behaviour during development, and the factors leading to their dysregulation in disease, remain the subject of interest and debate. Lately, advances in single-cell genomics have shifted emphasis towards the elucidation of molecular regulatory programmes and transcriptional cell states. However, quantitative statistical approaches based on cell lineage tracing data have provided fresh insight into stem and progenitor cell behaviour, questioning the role of cell fate stochasticity, transcriptional heterogeneity and state priming. These investigations, which draw upon conceptual insights from statistical physics and mathematics, provide a novel, generic and rigorous framework to resolve and classify stem cell self-renewal strategies, which heavily constrain, but do not seek to define, underlying molecular mechanistic programmes. Here, using epithelial maintenance as an example, we consider the foundation, conceptual basis, utility and limitations of such quantitative approaches in cell biology. Highlights: Collective dynamics of molecules or cells can give rise to "emergent" quantities. Methods from statistical physics allow identifying these degrees of freedom. Scaling and universality are useful concepts to study cell fate regulation. These concepts are exemplified in the context of clone dynamics in mouse epidermis.